Intraperiplasmic growth of Bdellovibrio bacteriovorus 109J: solubilization of Escherichia coli peptidoglycan. - Thomashow, M F (1978)
During penetration of Bdellovibrio bacteriovorus into Escherchia coli, two enzymatic activities, a glycanase and a peptidase, rapidly solubilized some 10 to 15% of the E. coli peptidoglycan. The glycanase activity, which solubilizes peptidoglycan amino sugars, came to a sharp halt with completion of the penetration process. Peptidase activity, which cleaves diaminopimelic acid residues from the peptidoglycan, continued, but at a decreasing rate. By 90 min after bdellovibrio attack, some 30% of the initial E. coli diaminopimelic acid residues were solubilized and present in the culture fluid as free diaminopimelic acid. During bdellovibrio penetration some 25% of the lipopolysaccharide glucosamine was also solubilized by an as yet undefined enzymatic activity that yielded products having molecular weights below 2,000. The solubilization of E. coli lipopolysaccharide glucosamine also terminated at completion of bdellovibrio penetration. At the end of bdellovibrio growth, a second period of rapid solubilization of bdelloplast peptidoglycan began which resulted in lysis of the bdelloplast and complete solubilization of the peptidoglycan amino sugars and diaminopimelic acid. The final lytic enzyme(s) was synthesized just before the time of lysis.